Knowledge, attitude and practice of dentists in Coronavirus disease 2019 pandemic in Turkey - Fatih Mehmet Çoşkunses; Berkay Tokuç (Istanbul University, 2020)
Purpose: The aim was to assess the knowledge, attitudes and anxiety of the dentists in relation to COVID-19. Subjects and Methods: This cross-sectional survey was conducted amongst 590 dentists employed in Turkey from March to April 2020. The electronic survey consisted of 22 questions related to demographic profile, knowledge, clinical practice and anxiety level of the participants towards dental management of COVID-19. The survey was sent to participants by email and mobile phone messages to be filled electronically. Results: Majority of respondents pointed to aerosol (98.5%), saliva (90.6%) and mucosal contact (71.4%) as the transmission routes of COVID-19. Amongst all clinical symptoms of the disease questioned, fever (99.8%), dry cough (99.1%), fatigue (90.0%) were associated with COVID-19 by vast majority of population. 96.4% of respondents agreed the usage of gloves as personal protective equipment and it was followed by face shield (88.1%), disposable gown (83.4%), protective goggles (73.9%). Increased usage of FFP2/N95 (33.9%) and FFP3/N99 (10.9%) respirators, contrary to reduction of surgical mask usage (50.7%), were observed in aerosol-generating procedures comparing to dental procedures without producing aerosol and these differences were highly significant (p<0.001, p=0.004, p<0.001). The mean anxiety level of respondents was 3.35 ± 1.18 (ranging from 0 to 5). Conclusion: These results demonstrated an adequate knowledge, especially in clinical symptoms of COVID-19 amongst dentists. However, the respirator usage rate in aerosol-generating procedures was not satisfactory which suggesting to necessity of dentists' education about pandemic.